Fostering Environmental Ethics: The Role of Integrated Digital and Eco-Literacy in Islamic Education - Moh. Sobirin; Saepudin Saepudin; Mokhamad Miptakhul Ulum (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2024)
The accelerating advancement of digital technology and artificial intelligence in the Fourth Industrial Revolution demands Islamic Education (PAI) to develop students’ digital competence and critical engagement. Simultaneously, worsening environmental degradation highlights the urgent need for educational models that integrate Islamic theological values with eco-literacy to foster ethical and sustainable behavior. This study examines the effectiveness of integrating digital literacy and eco-literacy into the Islamic Education (PAI) curriculum to transform the values of tawḥīd into students’ environmental ethics in Madrasah Aliyah across Tegal Regency. The study is grounded in the context of global environmental crises and the dynamics of the Fourth Industrial Revolution, which require Islamic education to produce a generation that is not only faithful but also environmentally responsible and digitally adaptive. The purpose of this research is to measure the effectiveness of the integration model in enhancing students’ understanding of tawḥīd, environmental attitudes, and environmentally ethical behavior, as well as to assess the role of artificial intelligence (AI) technology in the learning process. A quasi-experimental method using a pretest–posttest control group design was employed with 240 students assigned to experimental and control groups. Instruments included a tawḥīd comprehension test, an environmental attitude scale, behavioral observations, and a digital literacy assessment. The findings reveal significant improvements in all three variables in the experimental group compared to the control group, with tawḥīd comprehension serving as a partial mediator between digital literacy and environmental behavior. AI-based tools enhanced student engagement and personalized learning, effectively supporting the internalization of Islamic values. These results reinforce the theoretical framework of integrating digital literacy and eco-literacy as an innovative educational approach in Islamic Education and highlight its potential as a pedagogical strategy responsive to technological advancements and contemporary environmental challenges.